Hubungan Kebiasaan Bermain Game Online di Rumah dengan Sikap Disiplin Beribadah Peserta Didik pada Pembelajaran PAI di SDN No. 138 Inpres Manggulabbe Kabupaten Takalar - Syarif, Anita; Marjuni; Saprin (Primer Edukasi Journal, 2024)
This research aims to describe: (1) What is the habit of playing online games, (2) What is the disciplined attitude towards praying, and (3) Is the habit of playing online games at home related to the disciplined attitude towards praying of students in PAI learning at SDN No. 138 Inpres Manggulabbe Takalar Regency. This research uses a quantitative approach, namely a process of finding knowledge by using data in the form of numbers as a tool to find information about what you want to know. The type of research used is correlational research. The population of this research is students who have a habit of playing games with a total of 220 students. The sample in this study was 41 people. The instruments in this research are questionnaires and documentation. The instrument was tested for validity using validity and reliability tests, and analyzed using descriptive tests and inferential tests. From the research results, there is a negative and positive relationship between X variable, habit of playing online games at home, with Y variable, the disciplined attitude of prayer worship of students at SDN Inpres No. 138 Manggulabbe Takalar Regency.